The role of the programs of the Deanship of Scientific Research at King Saud University in developing the research skills of the students - bin Hwaimel, Nawal Abdulaziz (Journal of Educational and Psychological Sciences, 2018)
The objective of the research is to identify the role of the Deanship of Scientific Research programs at King Saud University in developing the research skills of postgraduate students in the humanitarian faculties. The researcher relied on the descriptive descriptive method and the questionnaire as a research tool that was distributed to a sample of (351) female graduate students at King Saud University in the humanitarian colleges. Using the statistical program (SPSS), the research reached the following results: Scientific research at King Saud University in the development of research skills on the average of (2.87) of (5) with the estimate (I agree to some extent), and at the level of axes, the axis (development of skills related to access to information among students) , 90), with a grade (I agree to a certain extent) followed by a (Development of skills related to writing research) (2.85), an estimate (I agree to some extent), and finally the development of skills related to students’ In the statistical analysis of female students and obtained an average of (2.82), with grade (I agree to some extent). There were statistically significant differences at (α0,05) in the responses of members of the research community for the benefit of the members of the research sample in the master stage. There were statistically significant differences at the level of (α0,05) in the responses of the members of the research sample in the faculties of (Education, Arts) and the responses of members of the research community in the faculties of Business Administration, Political Science and Law, Tourism and Archeology, Education, Arts). In light of the results, the researcher recommended a number of recommendations to develop the research skills of the students, including: Increasing the seminars, training courses and workshops offered by the Deanship of Scientific Research within the university. And to benefit from the staff members with high experience in the programs of the Deanship; to serve the postgraduate students, and provide assistance, and answer their questions. And to make the most of the means of social communication; to reach the largest possible segment of postgraduate students. And to hold periodic meetings with graduate students; to introduce the services of the Deanship.